Analisis Vegetasi Tumbuhan Herba Di Kawasan Hutan Krawak - Dede Nuraida; Sheilla Zulfaiza Arbiyanti Rosyida; Niken Ayu Widyawati; Kristin Winda Sari; Moh. Rizal Iwan Fanani (Universitas Nusantara PGRI Kediri, 2022)
Krawak forest is a protected forest that function to regulate water management, prevent fliooding and erosion, and maintain soil fertility. One of the plant habitus that contributes to the vegetation in the Krawak Forest is herbs. The existance of herbaceous plants in Krawak Forest is quite diverse, but so far there is no information about the species composition and diversity. This study aims to analyze the vegetation of herbaceous plants in the Krawak Forest by calculating species density, important value index, and diversity. The research was carried out on April 26, 2022.The type of research is quantitative descriptive, the sampling method is the quadratic method with a size of 1mx1m with 4 plots. Data collection techniques were carried out by recording the name and number of each species found in the plot, as well as the area covered by each species. Data analysis was carried out by calculating species density, dominance, and frequencys as the basis for calculating the important value index of each species. In addition, the Shannon-Wiener diversity index was also calculated to determine the level of diversity of herbaceous plants in the forest. The results of the study found 13 species of herbaceous plants belonging to 8 families, each family having a number of varied species as well as the number of individuals in each species.The highest species density was owned by Typhonium flagelliforme with a value of 38.36 and the lowest was Digitaria sanguinalis, Commelina benghalensis, and Verbesina alternifolia with the same value of 1.37. The highest important value index was Chromolaena odorata with a value of 54.60 and the lowest was Digitaria sanguinalis and Verbesina alternifolia with a value of 6.91. The diversity index obtained a value of 2.14 where this value indicates the level of forest diversity in Krawak forest is in the medium category.